Utilization of European Funds in the Public Administration. Study case - Galati County Council - Manuela Panaitescu (EIRP Proceedings, 2014)
The main objectives of this paper are to reveal some aspects regarding European funds‟ utilization, starting with the comprehension of EU philosophy regarding cohesion policy and emphasizing the important role played by Structural and Cohesion Funds for public administration, especially in times of economic downturn when the financial resources are difficult to access. Prior Work: this work continues prior research carried out for the “European Programs and Projects Management” MA thesis. Approach: The main methods employed for capturing the research evidence consists in management strategies analysis in the public administration, especially in studying the capacity of absorption of European funds in the case Galati County Council. The main results of this paper show that the risks of absorption capacity decrease of EU funds are linked to a number of factors, such as financial problems, poor information, lack of managerial experience, etc.